Mutu Pelayanan Keperawatan Berhubungan dengan Kepuasan Pasien - Silvia Ni Nyoman Sintari; Putu Gede Subhaktiyasa; Kiki Rizki Fista Andriana (Public Inspiration : Jurnal Administrasi Publik, 2022)
The importance of maintaining the quality of health services. There is a problem of patient satisfaction, there are nursing health services that are obtained. The purpose of this study was to determine the relationship between the quality of nursing services and patient satisfaction. Correlation quantitative descriptive research design with a cross-sectional approach. The population is patients in RSX, the number of samples is 100 people using the slovin formula with purposive sampling method. The measuring instrument used is the Quality and Patient Satisfaction questionnaire. Data analysis using rank spearment test. The mean age of the respondents was 36.19 Â±13.60 years. Most of the respondents were female, 58 people (58%), high school education, 55 people (58%), who considered the quality of service to be adequate, 74 people (74%), and 55 people (55%) rated patient satisfaction in the satisfied category. the results of the analysis of quality variables with patient satisfaction obtained p value of 0.017 (p 0.05). The results showed that there was a relationship between the quality of nursing services and patient satisfaction. This is due to the good quality of the nursing services provided and the satisfaction of patients with the services they receive, thus creating the same perception between quality and service, the better the quality, the better satisfaction.